KEBERDAYAAN PETANI MELALUI KELOMPOK TANI PADI SAWAH DI DESA MANDOKE KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Hikmah Hikmah; Awaluddin Hamzah; La Ode Kasno Arif (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
Agriculture, particularly the cultivation of rice in Southeast Sulawesi, plays a pivotal role in ensuring national food security and driving economic growth. However, the decline in production in Mondoke Village is indicative of the limited empowerment of farmers, which can be attributed to a number of factors, including inadequate awareness, insufficient assistance, an insufficient readiness to face obstacles, and a lack of cooperation within farmer groups. The objective of this study is to ascertain the extent of rice farmers' empowerment in Mondoke Village, Lambandia District, East Kolaka Regency. The research population consists of 50 rice farmers who are members of farmer groups in Mandoke Village. The research sample was obtained through the census method.  The data collection techniques employed in this study included in-depth interviews, documentation review, and survey questionnaires. The independent variable in this study was farmer empowerment. The data were processed using class interval and percentage formulas, and then analyzed descriptively and quantitatively. The findings indicated that the empowerment of rice farmers in Mondoke Village fell within the moderate category. Some farmers exhibited high levels of awareness, training, and social networks, while others demonstrated limitations in terms of access, assistance, and technology application. While awareness and a readiness to change were found to be quite high, the effectiveness of the empowerment initiative was found to be hindered by an absence of sustainable external support. The capacity to augment capacity and gain access indicates that training is not yet fully relevant and ongoing, while market and technology access has been utilized individually rather than collectively. The capacity to surmount impediments remains limited due to inadequate planning, adaptation, and joint implementation. Despite the existence of practices involving the sharing of information and experiences among farmers, optimal levels of solidarity and cooperation have yet to be achieved. This is primarily due to the absence of coordination among farmer groups and the lack of a synchronized planting schedule.